Cytomegalovirus Pathogenesis in Transplantation - Jane E Grundy (Canadian Journal of Infectious Diseases)
Cytomegalovirus (CMV) infection is an important cause of morbidity and mortality in the immunocompromised; however, even within this group of patients, infection with CMV is not synonymous with disease. A number of factors affect the pathogenicity of the virus. An understanding of the mechanisms by which CMV causes disease at different sites in the body, and of how U1at might vary with different patient groups, is essential to the design of stategies for the prevention and treatment of disease. This review discusses the factors which affect the occurrence and type of CMV disease in different patient populations, and considers some of the underlying mechanisms which might contribute to pathology.